2005
DOI: 10.1038/sj.bjc.6602517
|View full text |Cite
|
Sign up to set email alerts
|

The development and characterisation of porphyrin isothiocyanate–monoclonal antibody conjugates for photoimmunotherapy

Abstract: A promising approach to increase the specificity of photosensitisers used in photodynamic therapy has been through conjugation to monoclonal antibodies (MAb) directed against tumour-associated antigens. Many of the conjugations performed to date have relied on the activated ester method, which can lead to impure conjugate preparations and antibody crosslinking. Here, we report the development of photosensitiser -MAb conjugates utilising two porphyrin isothiocyanates. The presence of a single reactive isothiocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
117
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 24 publications
1
117
0
Order By: Relevance
“…Similar results were also reported in studies comparing aluminium tetrasulfophthalocyanine (AlPcS 4 ) immunoconjugates with a noninternalizing MAb 35A7 recognizing carcinoembryonic antigen (CEA) and an internalizing HER2 MAb FSP 77 and 17.1A. 96,97 This hypothesis was further tested with two hydrophilic photosensitizers. 98,99 The rationale for using hydrophilic photosensitizers is obvious, because this type of photosensitizer generally has low photocytotoxicity due to low cell membrane affinity, and they are good candidates for photoimmunoconjugation because of good water solubility.…”
Section: Growth Factor Receptorssupporting
confidence: 58%
“…Similar results were also reported in studies comparing aluminium tetrasulfophthalocyanine (AlPcS 4 ) immunoconjugates with a noninternalizing MAb 35A7 recognizing carcinoembryonic antigen (CEA) and an internalizing HER2 MAb FSP 77 and 17.1A. 96,97 This hypothesis was further tested with two hydrophilic photosensitizers. 98,99 The rationale for using hydrophilic photosensitizers is obvious, because this type of photosensitizer generally has low photocytotoxicity due to low cell membrane affinity, and they are good candidates for photoimmunoconjugation because of good water solubility.…”
Section: Growth Factor Receptorssupporting
confidence: 58%
“…21 Antibody fragments such as scFvs (single-chain Fv fragments) have been shown to be superior to whole antibodies in many aspects of tumor targeting such as speed of penetration and tumor:normal tissue specificity, 22,23 making them ideal vehicles for targeted PDT if sufficient numbers of PS can be attached to these small 30 kDa proteins. Photocoagulation of ocular vasculature 24 and tumor destruction 25 have been demonstrated by Neri and coworkers using the antibody fragment L19; however, this and other research 17 illustrates the challenge in that only 1-2 PS molecules could be attached directly to L19.…”
mentioning
confidence: 99%
“…14 Photosensitizers conjugated to whole antibodies can target a range of cancers 12 or pathogens 15 ; however, experiences so far has shown that many technical problems exist in coupling high numbers of PS to whole antibodies. These include impaired antibody binding, reduced solubility [16][17][18][19] and unfavorable pharmacokinetics due to the resulting high molecular weight of such photoimmunoconjugates (PICs). Some researchers have tried using carrier moieties such as branched carbohydrate or polylysine chains, which are in turn linked to the antibody.…”
mentioning
confidence: 99%
“…21) (Pereira et al 2014a). In fact, porphyrins and their derivatives conjugated with human and bovine serum albumin (HSA and BSA, respectively) have been successfully prepared and have demonstrated remarkable cell type specificity towards tumoral macrophage-like cells when compared to cancer cells (Hamblin and Newman 1994, Sutton et al 2002, Hudson et al 2005. This fact, was justified by the high accumulation of albumin in tumor tissues due to the EPR effect (enhanced permeability and retention of macromolecules in tumor tissues) (Kratz 2008, Maeda et al 2000.…”
Section: Cancer Pdt and Porphyrin-type Derivatives 1003mentioning
confidence: 94%
“…It takes into consideration the improvement mainly related with PS transport and specificity for tumors (Josefsen andBoyle 2008, Senge 2012). New or already known PSs are conjugated, for example, with antibodies (Kudarha and Sawant 2017, Hudson et al 2005, Pereira et al 2014 or nanoparticles (Yang et al 2017, Ma et al 2017). Targeting strategies have already shown that the PS affinity for tumors increases in significant ways.…”
Section: Development Of Photosensitizersmentioning
confidence: 99%